Computational Study on Effect of Obstacles in Pulse Detonation Engine - Tripathi, Saurabh; Murari Pandey, Krishna; Randive, Pitambar (International Journal of Engineering and Technology, 2018)
Deflagration to Detonation transition is an important factor in the operation of pulse detonation engine which is basically working on the constant volume cycle. Insertion of obstacles decreases the DDT length. Hydrogen and the oxygen-enriched air was used as fuel and oxidizer respectively. The Purge gas is not required used. K-Ô‘ turbulence model is being used for the simulation and for combustion species transport model is being used. Effect of blockage ratio and obstacle spacing is also discussed. A blockage ratio of 0.5 is considered for the Shchelkin spiral. Temperature profile, flame propagation velocity and average peak pressure variation are discussed. Two-dimensional geometry and Shchelkin shape of obstacles are being considered. The comparison is done between straight tube and tube with obstacles. Numerical simulation is done and the results are being compared with those obtained through experimental investigation.Â Â